Analysis Of Government Expenditure On Gross Regional Domestic Product In Eastern Kalimantan - Fitri Agustina; Anna Khairunnissa; Ahmad Fiqri Pratama; Ratu Eva Febriani (Journal of Research in Social Science and Humanities, 2024)
Government spending plays a crucial role in a region's economy, especially in Eastern Kalimantan, which has a wealth of natural resources becoming one of the main drivers of the Indonesian economy. The study aims to analyze the influence of government spending on Gross Regional Domestic Product (GRDP) in Eastern Kalimantan from 2010-2023. The dependent variable of the study is regional gross domestic product while the independent variable is health spending, education expenditure, public service spending and housing and public facilities spending. The research method used is a double linear regression analysis with time series data. The results of the study show that government spending on education, public services and housing, and public facilities has a significant influence on the increase in GRDP in Eastern Kalimantan. It highlights the importance of strategically allocating government spending to boost the regional economy.